Characteristics of the length of the radius and ulna in children - Wu, Chunxing; Wang, Dahui; Mo, Yueqiang; Zhang, Zhiqiang; Ning, Bo (Frontiers in Pediatrics, 2022)
Objectives: Congenital malformation, trauma, tumor, or metabolic disease can cause length deformity of the radius or ulna, affecting the appearance and function of the forearm. Osteotomy and lengthening with external fixation can obviously improve the length of the radius and ulna (LRU). However, the extent of lengthening required is still unclear. This study analyzed the LRU in children, to provide suggested standards for various orthopedic treatments. Methods: Normal LRUs were measured on X-ray images in children who came to hospital for emergency treatment, with measurements including anterior–posterior (AP) radiographs, lateral (LAT) radiographs, full LRU (total length), and LRU without the epiphysis (short length). Any cases of fracture or deformity affecting measurement were excluded. Three hundred twenty-six cases were divided into 16 groups according to age from 1 year old to 16 years old. Results: The earliest epiphyseal plate and ossification center were observed in the distal part of the radius at 1 year old, and in the proximal part at 3 years old in both boys and girls. In the ulna, at the distal end it was 6 years old in girls and 7 years old in boys, while in the proximal part ossification was observed at 9 years old in both boys and girls. The proximal epiphyseal plate of the ulna began to close on X-ray images at 12 years old in girls and 13 years in boys. LRU increased with age, and there was a strong positive correlation and consistent ratio between radius, ulna and age. In short length, the ratio of the length of radius to ulna (RLRU) ranged from 0.8941 to 0.9251 AP, from 0.8936 to 0.9375 LAT. In total length, RLRU ranged from 0.9286 to 0.9508 AP, and 0.9579 to 0.9698 LAT. Conclusions: The length and epiphyseal ossification of the radius and ulna are associated with age. RLRU is also limited to a certain range and tends to remain stable with age. These characteristics have clinical significance for deformity correction of the forearm.